Chinese Students' Expectations of Postgraduate Study Experience at UK Universities in the Context of Higher Education Marketisation - Dai, Sicheng (2022)
The purpose of higher education as it relates to marketisation has gradually shifted towards providing students with satisfactory services and improving their experience at and meeting their expectations of higher education. A clear sign of this trend can be seen in the shift from students being learners to students being consumers, which is increasingly evident in UK higher education. Against this background, some scholars argue that the essence of higher education has to some extent been undermined. Furthermore, the excellent quality of research and education at UK universities attracts an increasing number of Chinese students to undertake their postgraduate studies in the UK. Consequently, Chinese students have become a significant proportion of UK higher education. Hence, this research aims to explore the expectations of Chinese postgraduate students’ expectations of their higher education experience while studying at UK universities in the context of the marketisation of higher education.